Choosing cloud hosting for a growing and dynamic organization : Fortis Healthcare - Verma, Sanjay, (SAGE Business. Cases., 2019)
Fortis Healthcare was one of the biggest healthcare providers in India with the best in class medical technology. However, when it came to managing information systems, none of its units functioned in a way befitting the organization's stature. Varun Sood joined Fortis as Chief Information Officer in November 2012 and landed in an entirely dysfunctional IT department. He saw that the department lacked proper structure with no role clarity amongst the employees. Work assignments were random and not based on the role the person played in the project. Many projects failed; including one mega project on HIS (Hospital Information System). The primary reason was the lack of control over the progress of the project especially in terms of time and budget. Overshooting time and budget did not raise any alarms in the hospital. The IT department's reputation was in the pits.